The Role of Novelty and Prior Art in the First to File System to Protect Traditional Knowledge from Invalid Patent Claims - Ramadhan, Muhammad Citra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the role of novelty and prior art in the first to file system to protect traditional knowledge from invalid patent claims. Traditional knowledge is part of a valuable cultural heritage. Protecting it means maintaining and preserving the cultural identity of a community. In reality, most of the traditional wealth that was once owned by the people of the archipelago has been lost or moved to other countries. The study uses normative legal methods. Data collection was carried out through literature studies, observations, and document analysis. The results of the study show that in the First to File system, patent rights are granted to the first party to file a patent application, not the first party to create an invention. In the context of protecting against invalid patent claims on traditional knowledge, it is important for communities or countries to document their traditional knowledge as prior art. With adequate documentation, it can be shown that the knowledge existed before any patent claims were filed by other parties. So that it can protect traditional knowledge from invalid patent claims. Overall, the concept of novelty and prior art in the first to file system functions as a mechanism to ensure that traditional knowledge that has existed for a long time cannot be patented by unauthorized parties.